Molecular effects of free and doxorubicin-loaded aragonite calcium carbonate nanoparticles on MCF-7 cell lines - Ahmed, Hamidu (2019)
Cancer is one of the prime causes of death and breast cancer is the most erratic malignant disease which causes serious burden to women worldwide. Cockle shell- derived aragonite calcium carbonate nanoparticles (Ar-CC-NPs) encapsulated with doxorubicin (DOX) has transpire as an efficacious therapy against breast tumour, but still the use of targeted therapy in cancer treatment appears to be ineffective and often associated with some set back, hence necessitates the need for improved targeted therapy. This study determines the therapeutic potential of doxorubicin- loaded aragonite CaCO3 nanoparticles using proteomic approach. For the proteomic study, Liquid Chromatography/Mass Spectrometry analysis (LCMS/MS) was employed to investigate the MCF-7 related protein in human breast cancer cells after treatment with the DOX and DOX-Ar-CC-NPs. Aragonite CaCO3 nanoparticles are synthesized from cockle shells and characterized for physiochemical properties using Transmission electron microscope (TEM), Field emission scanning electron microscope (FESEM), Zeta potential, Fourier transmission infrared (FTIR) and X- ray diffraction (XRD) techniques. The aragonite nanoparticles are synthesized from the cheaply available natural sea water cockle shells, which are cleaned with banana peels, homogenized and then stirred vigorously in dodecyl dimethyl betane (BS-12) solution using a rotary pulvering blending machine in order to reduce the a stringent temperature and unsafe chemicals associated with nanoparticles production and are then characterized for particle geometry using electron microscopy. An IC50 which is inhibitory concentration of 50% of the tested cells that signifies drug concentration, for the indication of cell viability was also determined and then, the synthesized aragonite calcium carbonate nanoparticles (Ar-CC-NPs) are then loaded with doxorubicin (DOX), an antineoplastic agent, which formed Doxorubicin-aragonite- nanoparticles (DOX-Ar-CC-NPs). The cytotoxic effect of DOX-Ar-CC-NPs was determined using superoxide dismutase commercial ELISA kit for cell membrane integrity, and flow cytometry, fluorescent imaging and electron microscopy for programmed cells death evaluation. Enzymes-linked immunosorbent assay was also used to assay oxidative stress biomarkers and apoptotic enzymes from MCF-7 cell treated using DOX-Ar-CC-NPs and the proteomic profile of cancer cell treated with DOX-Ar-CC-NPs are examined and evaluated the release profile, cytotoxicity and uptake, in pursuance of understand the molecular sound effects of free and DOX-Ar- CC-NPs on MCF-7 cell line and to further improve the anticancer effects of doxorubicin through early prediction and resolution of its drug resistance problems. The results of the study shows that Ar-CC-NPs with average diameter of 35.5 nm, 19.3% loading content and 97% encapsulation efficiency has a surface potential and intensity of -19 ± 3.9 mV and 100%, respectively. In addition, DOX-Ar-CC-NPs have an IC50 at 24, 48 and 72 hours of 1.829µg/mL, 0.902µg/mL and 1.0377µg/mL while that of DOX alone were 0.475µg/mL, 0.2483µg/mL and 0.0723µg/mL, respectively. However, even at higher concentration, no apparent toxicity was recorded with Ar-CC-NPs, which reveals its anticancer effect with MCF-7 cells with a viability of 92%. The DOX-Ar-CC-NPs had significant inhibitory effect on cell feasibility compared to DOX alone (p<0.05), similar trend was noticed in cellular apoptosis, oxidative stress markers and cellular uptake evaluation. However, treatment with DOX-Ar-CC-NPs significantly decreased the elevated level of superoxide dismutase 2 (SOD2) compared to untreated MCF-7 cells. Thus, the present findings revealed the capability of DOX-Ar-CC-NPs to induce apoptosis in MCF-7 cells, which indicates the high potency of Ar-CC-NPs in drug delivery. For the proteomic study, a total of 408 MCF-7 related proteins for DOX-Ar-CC-NPs and 128 proteins for DOX alone were identified from MCF-7 cells. The proteomic profiling analysis outcomes reveals new developments for the advancement of proteomics technologies which could yield a good result on discovery of potential significant breast cancer biomarkers for MCF-7 cells pertinent studies with archival samples. Shotgun LC-MS/MS studies could also serve to determine new biomarkers.